Initial training in pedagogy and emotions about mathematics: A research articulation in the fields of education and biomedical engineering (Revista Contexto & Educação, 2025)
This paper presents a case study that investigates the emotions of students of Degree in Pedagogy about mathematics. This is a mixed research, with a qualitative approach carried out as a narrative research in a focus group and with a quantitative approach based on an experiment that used a wearable electronic device to detect the heartbeats of the participating students. The results of the analysis of the data showed how the constituted narratives impacted on the revelation of the emotions of the undergraduate students in Pedagogy (manifested in their reports and in the signals detected by the device they used); how memories in relation to mathematics can produce teacher malaise and how this malaise can be registered, to be discussed, with the support of technological resources created from Biomedical Engineering. In addition to discussing how emotions about mathematics affect teachers in training when choosing their professional field, this article also presents an example of a research partnership between the areas of Education and Engineering to find solutions to problems related to teacher training.
Keywords: narratives; teacher malaise; biosensor; wearable electronic device